Surface Mold Brachytherapy for Scalp Dermatofibrosarcoma Protuberans in a Patient with Down Syndrome: A Case Report: Surface Mould HDR Brachytherapy for Scalp DFSP - Yilmaz, Sercan; Chaib Rassou, Salim; Tajammul, Syeda Sara; Mula-Hussain, Layth (Iraqi Journal of Cancer and Medical Genetics, 2026)
Dermatofibrosarcoma protuberans (DFSP) is a rare, locally aggressive soft tissue sarcoma arising from the dermis, representing approximately 0.1% of all malignancies. Although surgical excision with wide margins remains the standard treatment, local recurrence is common, particularly in patients with close or positive margins. Adjuvant radiotherapy is therefore recommended for recurrent disease or inadequate surgical margins. We report a rare case of scalp DFSP in a patient with Down syndrome treated using high-dose-rate (HDR) surface mold brachytherapy with the aid of three-dimensional (3D) printing technology. A 25-year-old woman with Down syndrome presented with recurrent DFSP of the right parieto-occipital scalp following an unplanned excision. Wide local resection with an occipital transposition flap and skin graft reconstruction confirmed DFSP with a deep positive margin involving the skull (R1). Owing to the curved scalp anatomy and the patient’s limited cooperation related to cognitive impairment, adjuvant HDR surface mold brachytherapy was selected. Treatment planning was performed using CT simulation under sedation. A 3D-printed skull model allowed the optimization of catheter placement without the need for further resimulation. A total dose of 32.5 Gy in five fractions was delivered using an Ir-192 radioactive source. Treatment was well tolerated, with only mild grade 1 dermatitis and partial alopecia. The irradiated tumor bed showed an initial complete response. Approximately twenty-two months later, a marginal recurrence developed at the edge of the surgical scar in the right temporal region, while the rest of the irradiated field remained free of disease. This nodule was removed by wide local excision, the multidisciplinary tumor board recommended observation, and the patient remained clinically free of recurrence at the most recent follow-up. Mild late effects included localized alopecia, hyperpigmentation, fibrosis, and thinning of the skin graft.